Pengaruh Debt to Equity Ratio, Return on Assets, dan Current Ratio terhadap Harga Saham - Hilmi Naufal Yasir; Erwin Budianto (Politeknik Ganesha Medan, 2026)
Stock prices in the food and beverage sector are influenced by fundamental financial performance, yet prior studies have shown inconsistent findings regarding the role of capital structure, profitability, and liquidity in explaining stock price movements. This study aims to examine the determinants of stock prices of food and beverage companies listed on the Indonesia Stock Exchange during 2021–2024 by emphasizing the role of Debt to Equity Ratio, Return on Assets, and Current Ratio within the post-pandemic market recovery context. Using a quantitative approach and multiple linear regression analysis, this study analyzed 56 observational data obtained from 14 selected companies through purposive sampling. The findings reveal that Return on Assets has a positive and significant effect on stock prices, while Debt to Equity Ratio and Current Ratio do not have significant partial effects. Simultaneously, the three financial ratios significantly influence stock prices. This study contributes to strengthening fundamental analysis and signaling theory by demonstrating that profitability remains the most relevant signal considered by investors in assessing firm value within Indonesia’s food and beverage sector. The findings also provide practical implications for investors to prioritize profitability indicators in investment decision-making, while companies are encouraged to improve asset efficiency to enhance market valuation..